COMMUNICATION EFFECTIVENESS OF ONLINE MEDIA GOOGLE CLASSROOM IN SUPPORTING THE TEACHING AND LEARNING PROCESS AT CIVIL ENGINEERING UNIVERSITY OF RIAU - Dhia Ghina Ramadhani Putri S; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Online media is one of the evolution of information and communication technology very rapidly at this time. The evolution of online media take a part in supporting for the learning process. Online media becomes one of the media that used to get some information and can be used as a learning resource. One of the online media is used as a learning resource is Google Classroom. Google Classroom is an application that allows the creation of classrooms in cyberspace. Google Classroom can be used for distribution of tasks, submit assignments and assess the tasks they have collected. Google Classroom also be used to provide information about lectures and upload learning materials. The theory used in this research are the effectiveness of communication as the main theories and new media as a supporting of the theory. The purpose of this research is to investigate how effective these online media in providing information on the Civil Engineering University of Riau. This research uses quantitative methods of data collection using a questionnaire that distributed to Civil Engineering students who are still actively using Google Classroom. Determination techniques for sample is using random sampling techniques. This results shows that the effectiveness of Google Classroom in Civil Engineering is considered very effective. This has been proved by the results of the data collected have been measured by six indicators, which are Receiver, Content, Media, Format, Source and Timing. The result is highly effective on a scale of 4.36, which means that Google Classroom is a very effective for used in providing information on the Civil Engineering University of Riau. Keyword: Communication Effectiveness, Online Media, Google Classroom, Civil Engineering